American scream : Allen Ginsberg's Howl and the making of the Beat Generation - Raskin, Jonah, 1942- (Berkeley : University of California Press, 2004)
Written as a cultural weapon and a call to arms, Howl touched a raw nerve in Cold War America and has been controversial from the day it was first read aloud nearly fifty years ago. This first full critical and historical study of Howl brilliantly elucidates the nexus of politics and literature in which it was written and gives striking new portraits of Allen Ginsberg, Jack Kerouac, and William Burroughs.
Poetickall Bomshell -- Family Business -- Trilling-esque Sense of "Civilization" -- Juvinescent Savagery -- Just like Russia -- Ladies, We Are Going through Hell -- Another Coast's Apple for the Eye -- Mythological References -- Famous Authorhood -- This Fiction Named Allen Ginsberg -- Best Minds.
Includes bibliographical references (pages 231-262) and index.
Print version record and CIP data provided by publisher; resource not viewed.
English.
JSTOR
Keywords: Ginsberg, Allen, -- 1926-1997.; Ginsberg, Allen, -- 1926-1997 -- Knowledge and learning; Ginsberg, Allen, -- 1926-1997 -- Psychology; Ginsberg, Allen, -- 1926-1997.; Ginsberg, Allen, -- 1926-1997 -- Et la psyhologie; Ginsberg, Allen, -- 1926-1997 -- Psychologie; Ginsberg, Allen, -- 1926-1997; Howl (Ginsberg, Allen); Ginsberg, Allen; Literature and mental illness -- United States -- History -- 20th century; Poetry -- Psychological aspects; Mental illness in literature; Beats (Persons); Littérature et maladies mentales -- États-Unis -- Histoire -- 20e siècle.; Poésie -- Aspect psychologique; Maladies mentales dans la littérature.; Beatniks; Beat generation; POETRY -- American -- General; LITERARY CRITICISM -- American -- General; Learning and scholarship; Beats (Persons); Literature and mental illness; Mental illness in literature; Poetry -- Psychological aspects; Psychology; United States; Beatgeneration; Howl (Ginsberg); Beat Generation; 1900-1999; 20th century; allen ginsberg; america; american culture; american poetry; american poets; american society; art and literature; beat generation; beat movement; beat poets; cold war america; controversial; critical analysis; cultural history; historical review; howl; jack kerouac; lit scholars; lit studies; literary criticism; literary figures; literary movements; modern poetry; new york; political literature; psychiatry; repressive society; san francisco